Comparison between Ultrasound Finding and Histopathological Study of Thyroid Nodule - Alshabeeb, Ahmed Abdulbari Neamah; Alhatemi, Murtadha Moojid Hadi; Smaysim, Ali Liwaa Abdulsahib (Academic Journal of Clinicians, 2025)
Background: Thyroid nodule is defined as a focal well-defined area of altered echogenicity within thyroid gland that is radiologically distinct from surrounding normal thyroid parenchyma. Thyroid nodule occurs with relatively high frequency in general population. Aim of the Study: To assess the accuracy of ultrasound in detection of malignant thyroid nodule and also to make use of ultrasound in early detection and screening Patients and methods: This retrospective study conducted at Al Sadr medical city and included 101 patients with thyroid nodules who were operated on during a period of thirty months. Collection of data was done preoperatively by ultrasound and calculation of ACR-TIRAD score and post-operative histopathological study after thyroid surgery. Results: A total of 101 patients with different thyroid nodules were enrolled in this study. Regarding the TIRADS levels of the studied group, it had been found that 13 patients had TR1, 38 patients with TR2, 27 patients had TR3, 20 patients had TR4 and 3 patients had TR5. The histopathology examination revealed that majority of the patients, 85/101 (84.2%), had benign nodules while 16 patients (15.8%) had malignant ones. Conclusions: Ultrasound was simple, noninvasive and easy to apply with good sensitivity and specificity and accuracy in detection of thyroid nodules.